Wireless Control and Monitoring of Industrial Processes by AVR and LabVIEW - Fadhil, Tamara Z. (Journal of University of Human Development, 2017)
This paper presents expansion, enhancement, design and implementation of wireless SCADA systems to control a variety of industrial processes from a master location which include authorizing vast monitoring for pipelines, natural gas, petroleum fields, water and transportation systems, chemical plants, utilities, oil refineries, power generation, electrical grid and an immense assortment of industrialization functionality. The control of environmental temperature, oil pressure, gases concentration, fuel tank level in power industrial plant had been collected and analyzed with a high power capacity 1 MW, based on Master terminal unit (MTU) design for data acquisition from Remote Terminal Unit (RTU) sensors and wireless data transfer using 2.4 GHz RF module, makes sensors data collection come true.